2011
DOI: 10.2182/cjot.2011.78.2.3
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment Tools for Evaluating Fitness to Drive: A Critical Appraisal of Evidence

Abstract: Seventeen measures met the inclusion criteria. Evidence suggests many tools do not have cutoff scores linked with on-road outcomes, although some had stronger evidence than others. Implications. When making a determination regarding driver fitness, clinicians should consider the psychometric properties of the tool as well as existing evidence concerning its utility in predicting on-road performance. Caution is warranted in using any one office-based tool to predict driving fitness; rather, a multifactorial-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…Unsworth (2011) describes the results of a pilot study, investigating the use of a head mounted video camera, which records an occupational therapist's comments during a driving evaluation, as a means of prompting recall of clinical reasoning. Vrkljan, McGrath, and Letts (2011) provide a review of assessments, identified as appropriate for evaluating safe driving behaviours. Winters and colleagues (2011) present a safe driving assessment model that guides the comprehensive evaluation of driving behaviours.…”
Section: T He Canadian Association Of Occupational Therapists' Nationmentioning
confidence: 99%
“…Unsworth (2011) describes the results of a pilot study, investigating the use of a head mounted video camera, which records an occupational therapist's comments during a driving evaluation, as a means of prompting recall of clinical reasoning. Vrkljan, McGrath, and Letts (2011) provide a review of assessments, identified as appropriate for evaluating safe driving behaviours. Winters and colleagues (2011) present a safe driving assessment model that guides the comprehensive evaluation of driving behaviours.…”
Section: T He Canadian Association Of Occupational Therapists' Nationmentioning
confidence: 99%
“…Edwards et al (2008) also found that, as expected, older drivers performed worse than younger drivers on the DHI. Other validation and reliability information for driver screening for the individual measures included in the DHI are summarized in detail by Vrkljan, McGrath, and Letts (2011).…”
mentioning
confidence: 99%
“…Assessing a person's ability to return to driving is complex even professionally, and there is still a lack of consensus in determining driving fitness and capacity (Vrkljan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The resumption of driving and the process of assessing an individual's fitness to drive is another area where there is a lack of standardisation of protocols and guidelines (Bottari et al, 2012;Classen et al, 2009;Vrkljan, McGrath, & Letts, 2011). Fitness to drive can be defined as having the ability to manage, anticipate and act on traffic situations and demands without risk (Austroads, 2012;Johnston, Goverover, & Dijkers, 2005).…”
Section: Assessment Of Fitness To Drivementioning
confidence: 99%
See 1 more Smart Citation